Mencari Keadilan: Dinamika Penanganan Kasus Pencabulan terhadap Anak Perempuan di Denpasar - Ni Kadek Ayu Puspita Dewi; Ni Ketut Sri Ratmini; I Gusti Ayu Jatiana Manik Wedanti (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Sexual violence against children is a multidimensional problem that intersects with legal, social, and psychological domains, particularly concerning girls as the most vulnerable group. This article is situated within the discourse of criminal law and child protection, aiming to examine the causes of obscene acts against girls in Denpasar City and the forms of legal protection provided to the victims. This study employs an empirical legal approach, with research conducted at the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) and Denpasar City Police (Polresta Denpasar). Data were collected through observation, structured interviews, and literature study. The findings indicate that acts of molestation are influenced by internal factors such as psychological vulnerability, and external factors such as lack of parental supervision, low education levels, and negative environmental influences. The resulting impacts are severe, both physically and psychologically. The legal protection provided includes juridical and non-juridical aspects, implemented by institutions such as UPTD PPA and the Police's Women and Children Protection Unit.